2016
DOI: 10.5897/ajb2015.15037
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of Haloxylon salicornicum on hepatic and renal functions of Wistar rats exposed to aluminium

Abstract: Aluminium is present in some manufactured medicines and foods. It is known that aluminium causes oxidative stress. Therefore, the present study was undertaken to determine the effectiveness of Haloxylon salicornicum extract in modulating aluminium chloride (AlCl 3) induced oxidative stress in rats. Male rats (40 to 50 g) were divided into four groups of six animals each. The experimental protocol was based on the administration of AlCl 3 (30 mg/kg/body weight) intraperitoneally (ip) every 5 days for 15 days. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Recent animal and clinical studies have reported that Al causes neuropathological changes in the central nervous system [5]. Al can accumulate in the liver and kidneys, causing hepatorenal toxicity [6]. Al also has prooxidative, excitotoxic, immunogenic, proinflammatory, and mutagenic effects [7].…”
Section: Introductionmentioning
confidence: 99%
“…Recent animal and clinical studies have reported that Al causes neuropathological changes in the central nervous system [5]. Al can accumulate in the liver and kidneys, causing hepatorenal toxicity [6]. Al also has prooxidative, excitotoxic, immunogenic, proinflammatory, and mutagenic effects [7].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, aluminum pots represent around 20% of the relative multitude of pots on the planet. Aluminum is additionally present in water suitable for human use with a convergence of 0.2 mg/L, water-filtering specialists, jars and containers, foil paper made from aluminum, and beauty care products (Fatima et al 2016 ). Thusly, human beings are highly susceptible to aluminum toxicity as it may accumulate in the kidney causing nephrotoxicity due to its high availability (Fatima et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Aluminum is additionally present in water suitable for human use with a convergence of 0.2 mg/L, water-filtering specialists, jars and containers, foil paper made from aluminum, and beauty care products (Fatima et al 2016 ). Thusly, human beings are highly susceptible to aluminum toxicity as it may accumulate in the kidney causing nephrotoxicity due to its high availability (Fatima et al 2016 ). Additionally, aluminum can liberate receptive oxygen species (ROS) and apoptosis by animating the favorable to oxidant effects of iron and copper, resulting in mitochondrial dysfunction and subsequent oxidative deterioration of macromolecules and releasing of cytochrome C from the mitochondria (Al-Olayan et al 2015 ; Zahedi-Amiri et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…[10,11] The generated ROS, in turn, can lead to lipid peroxidation perturbing the membranous integrity, oxidative damage of protein and nucleic acid. [12,13] Various tissues are reported to be the target of Al-induced effects. The induced oxidative stress by Al ultimately causes harmful effect on liver, [14] kidney, heart, reproductive organs and nervous system causing degenerative impacts.…”
Section: Introductionmentioning
confidence: 99%